Vertical farming goes dynamic: optimizing resource use efficiency, product quality, and energy costs - Kaiser, Elias; Kusuma, Paul; Vialet-Chabrand, Silvere; Folta, Kevin M.; Liu, Ying; Poorter, Hendrik; Woning, Nik; Shrestha, Samikshya; Ciarreta, Aitor; Van Brenk, Jordan; Karpe, Margarethe; Ji, Yongran; et al. (Frontiers in Science, 2024)
Vertical farming is considered a key enabler for transforming agrifood systems, especially in or nearby urbanised areas. Vertical farming systems (VFS) are advanced indoor cropping systems that allow for highly intensified and standardized plant production. The close control of environmental parameters makes crop production stable and repeatable, ensuring yearround uniform product quality and quantity irrespective of location. However, due to continuous changes in plant physiology and development, as well as frequent changes in electricity prices, the optimum conditions for crop production and its associated costs can change within minutes to days. This makes it beneficial to dynamically adjust setpoints for light (intensity, spectrum, pattern, and daylength), CO2, temperature, humidity, air flow, water, and nutrient availability. In this review, we highlight the beneficial effects that dynamic growth conditions can have on key plant processes, including improvements in photosynthetic gas exchange, transpiration, organ growth, development, light interception, flowering, and product quality. Our novel findings based on modelling and experimentation demonstrate that a dynamic daily light intensity pattern that responds to frequent changes in electricity prices can save costs without reducing biomass. We further argue that a smart, dynamic VFS climate management requires feedback mechanisms: several mobile and immobile sensors could work in combination to continuously monitor the crop, generating data that feeds into crop growth models, which generate climate setpoints. In addition, we posit that breeding for the VFS environment is at a very early stage and highlight traits for breeding for this specialized environment.